Annular and central heavy pigment deposition on the posterior lens capsule in the Pigment dispersion syndrome - Turgut, Burak; Türkçüo?lu, Peykan; Deniz, Nurettin; Çatak, Onur (My University, 2008)
Purpose: To report annular and central heavy pigment deposition on the posterior lens capsule in a case of pigment dispersion syndrome. Methods: Case report. Results: A 36-year-old female with bilateral pigment dispersion syndrome presented with progressive decrease in visual acuity in the right eye over the past 1-2 years. Clinical examination revealed the typical findings of pigment dispersion syndrome including bilateral Krunkenberg spindles, iris transillumination defects, and dense trabecular meshwork pigmentation. Remarkably, annular and central dense pigmentation of the posterior lens capsule was noted in the right eye. Conclusion: Annular pigment deposition on the posterior lens capsule may be a rare finding associated with pigment dispersion syndrome. Such a finding suggests that there may be aqueous flow into the retrolental space in some patients with this condition. The way of central pigmentation is the entrance of aqueous to Berger's space. In our case, it is probable that spontaneous detachment of the anterior hyaloid membrane aided this entrance. © Springer Science+Business Media B.V. 2007.
Keywords: Anterior hyaloid membrane; Pigment dispersion syndrome; Pigmentation; Posterior lens capsule